2019
DOI: 10.1590/1983-1447.2019.20180016
|View full text |Cite
|
Sign up to set email alerts
|

Feridas em membros inferiores em diabéticos e não diabéticos: estudo de sobrevida

Abstract: Resumo OBJETIVO Avaliar a sobrevida de feridas em membros inferiores de pacientes diabéticos e não diabéticos. MÉTODO Estudo de coorte retrospectivo de pacientes com úlceras de membros inferiores tratados em centro especializado entre 2011 e 2013. Desfecho: cicatrização de lesões de membros inferiores em dias. Realizou-se análise da função de sobrevida das feridas de membros inferiores e das diferenças entre diabéticos e não diabéticos. Aplicou-se o teste Log-rank para comparação das curvas de sobrevida entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
7
Order By: Relevance
“…It is known about the difficulties of wound healing in diabetic patients. Retrospective cohort study, developed in Belo Horizonte, with people with lower limb ulcers, in the period from 2011 to 2013, found that 23% of individuals with DM healed their wounds, in the period of 600 days, while among non-diabetics, healing rate was around 63%, with an important statistical difference in relation to the survival of the 2 groups 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known about the difficulties of wound healing in diabetic patients. Retrospective cohort study, developed in Belo Horizonte, with people with lower limb ulcers, in the period from 2011 to 2013, found that 23% of individuals with DM healed their wounds, in the period of 600 days, while among non-diabetics, healing rate was around 63%, with an important statistical difference in relation to the survival of the 2 groups 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Gerar dados observacionais com um grupo maior de pacientes e adoção de modelo de pesquisa com ensaios clínicos controlados pode vir a ampliar o intervalo de confiança e revelar outros benéficos ou reações não conhecidas até o momento. 27 . Esses dados demonstram a eficácia da utilização do ozônio no tempo de reparo tecidual.…”
Section: Discussionunclassified
“…Já no grupo de pessoas sem diabetes o índice de cicatrização foi de 63%. A diferença mostra indícios de que há retardo na cicatrização de feridas em pacientes diabéticos (OLIVEIRA et al, 2019).…”
Section: Discussionunclassified